Damage Control for Vascular Trauma from the Prehospital to the Operating Room Setting - Pikoulis, Emmanouil; Salem, Karim M.; Avgerinos, Efthymios D.; Pikouli, Anastasia; Angelou, Anastasios; Pikoulis, Antreas; Georgopoulos, Sotirios; Karavokyros, Ioannis (Frontiers in Surgery, 2017)
Early management of vascular injury, starting at the field, is imperative for survival no less than any operative maneuver. Contemporary prehospital management of vascular trauma including appropriate fluid and volume infusion, tourniquets and hemostatic agents have reversed the historically known limb hemorrhage as a leading cause of death. In this context damage control surgery has evolved to damage control resuscitation (DCR) as an overarching concept that draws together preoperative and operative interventions aiming at rapidly reducing bleeding from vascular disruption, optimizing oxygenation and clinical outcomes. This review addresses contemporary DCR techniques from the prehospital to the surgical setting, focusing on civilian vascular injuries.